Surfing the brain. - Van de Ville, D. (IEEE Engineering in medicine and biology magazine)
In this paper, an overview with unification of techniques that deploy the wavelet transform in the spatial domain for the analysis of functional magnetic resonance imaging (fMRI) is presented.